2010
DOI: 10.1007/s10681-010-0295-8
|View full text |Cite
|
Sign up to set email alerts
|

A practical method for apple cultivar identification and parent-offspring analysis using simple sequence repeat markers

Abstract: Differentiation of cultivars with simple sequence repeat (SSR) markers is a very useful technique for the true-to-type characterization of cultivars and clarification of parent-offspring relationships. We developed an SSR marker set for cultivar identification comprising 15 markers that were screened from 46 previously published SSRs. This marker set could be used for apple varieties including Malus 9 domestica and/or other Malus species. These SSRs successfully characterized 95 apples, including the leading a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 24 publications
(28 reference statements)
0
22
0
1
Order By: Relevance
“…Numerous diversity studies have been performed on apple germplasm (Garkava-Gustavsson et al 2008;Gasi et al 2010;Gross et al 2014;Hokanson et al 2001;Liang et al 2015;Moriya et al 2011;Pereira-Lorenzo et al 2008;Song et al 2006;Urrestarazu et al 2012;van Treuren et al 2010) but as far as we know, the present study is the largest one to be performed so far at a national level with such a large number of SSR markers. Apple genetic resources are conserved by many very active structures in France (Fig.…”
Section: Discussion Gene Pool Representativeness and Geographical Strmentioning
confidence: 93%
See 1 more Smart Citation
“…Numerous diversity studies have been performed on apple germplasm (Garkava-Gustavsson et al 2008;Gasi et al 2010;Gross et al 2014;Hokanson et al 2001;Liang et al 2015;Moriya et al 2011;Pereira-Lorenzo et al 2008;Song et al 2006;Urrestarazu et al 2012;van Treuren et al 2010) but as far as we know, the present study is the largest one to be performed so far at a national level with such a large number of SSR markers. Apple genetic resources are conserved by many very active structures in France (Fig.…”
Section: Discussion Gene Pool Representativeness and Geographical Strmentioning
confidence: 93%
“…(Zhen et al 2004). These markers have proved advantageous for diversity studies on apple (Garkava-Gustavsson et al 2008;Gasi et al 2010;Gross et al 2014;Hokanson et al 2001;Liang et al 2015;Moriya et al 2011;Pereira-Lorenzo et al 2008;Song et al 2006;Urrestarazu et al 2012;van Treuren et al 2010), and several hundred SSR markers have been developed and genetically mapped across the 17 linkage groups of the apple genome (Gianfranceschi et al 1998;Liebhard et al 2002;Silfverberg-Dilworth et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Xuan et al (2009) reported that the SSR fingerprinting using the 15 Prunus SSRs successfully separated the 43 sweet-and 30 sour cherry cultivars. Furthermore, 21 apple cultivars had been distinguished from each other by three SSR markers (Guiffordet al, 1997), whereas Moriya et al (2011) using 15 SSR markers successfully identified 95 apple cultivars. In addition, for the study in Tunisian apricots, five microsatellite primers and the 28 resulting alleles were sufficient to discriminate among all 54 apricot cultivars (Krichen et al, 2006).…”
Section: High Efficiency In the Identification Of Apricot Germplasms mentioning
confidence: 99%
“…Therefore, it is also important to confirm parent-offspring relationships for cultivars by using traditional molecular markers and to provide the correct pedigree information for use in fruit tree breeding programs. In perennial fruit tree species, discrepancies in parent-offspring relationships of some cultivars have been found and corrected by using molecular markers (Kimura et al, 2003;Kitahara et al, 2005;Matsumoto et al, 1999d;Moriya et al, 2011;Ninomiya et al, 2015;Sawamura et al, 2004Sawamura et al, , 2008Yamamoto et al, 2003). However, citrus cultivars developed in the NIFTS breeding program have generally not been investigated to confirm their parent-offspring relationships, even though they have frequently been used as parents in other breeding programs.…”
Section: Introductionmentioning
confidence: 99%